Green Human Resource Management and AI Adoption in SMEs: A Conceptual Study of Sustainable Workforce Transformation in Indonesia’s Emerging Market - Stefanie Inggried Gorap; Josafat Gracia Ginting (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This conceptual paper examines how the integration of Green Human Resource Management (GHRM) and Artificial Intelligence (AI) can drive sustainable workforce transformation in Indonesia’s emerging market context, with specific reflection on small and medium-sized enterprises (SMEs) in Makassar, South Sulawesi. Responding to the parallel pressures of digitalization and sustainability, the study adopts a conceptual–descriptive design based on an integrative review of literature published between 2018 and 2024 on GHRM, AI in HRM, sustainable HRM, and SME transformation in emerging economies. Drawing on approximately 20 core scholarly and policy sources, the paper develops the GHRM–AI Sustainable Workforce Framework, which links leadership commitment, green HR practices, AI-enabled HR processes, and employee green–digital capabilities to economic, environmental, and social outcomes. The framework proposes that leadership commitment to sustainability and responsible AI use shapes the design of green HR processes, AI technologies amplify the effectiveness and measurability of these processes, and employee capabilities mediate their impact on triple-bottom-line performance. Contextual reflection on SMEs in Makassar highlights both opportunities such as growing digital adoption and policy support and constraints, including limited HR structures, capability gaps, and financial and infrastructural barriers. The paper contributes theoretically by extending GHRM discourse into the domain of AI-enabled digital transformation and practically by offering a strategic roadmap for SMEs, policymakers, and practitioners seeking to align HR strategies with sustainability and digital agendas. It also outlines directions for future empirical research to test, refine, and operationalize the proposed framework in diverse organizational and regional settings.